MODEL PEMBELAJARAN DAN PRINSIP BERMAIN PENCAK SILAT UNTUK ANAK PRASEKOLAH - Kriswanto, Erwin Setyo (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 79.4pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 240.7pt; mso-height-rule: exactly;">Abstract <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">The appropriate learning process for preschool <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">children is by playing. Playing is inconsciously part <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">of basic movement of pencak silat such as kicking, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">punching, eluding, or running. Not all of basic <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">movements in pencak silat are appropriate for <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">preschool children. Teachers need to be careful in <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">selecting or defining appropriate technique and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">movement. In delivering basic movements of pencak <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">silat for preschool children needs to include playing <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">methods and develops socialization aspects including <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">the use of language/ terminology modified in order <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">not to have violent impression. Children do not need <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">to be introduced about the concept of enemy, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">because the main aspect for them is to grow. Because <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">growing them needs stumulations so pencak silat is <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">only for fun, sport and discipline development, bot <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">for sefl-defense. In other words, it needs to consider <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">learning principals for preschool children. Leaning <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">pencak silat using playing methods can be done by <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">playing model, story telling, dancing, immitating <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">movement, or demonstrating something. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.65pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 561.7pt; mso-height-rule: exactly;">Kata kunci: Model pembelajaran, Prinsip bermain, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.65pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 561.7pt; mso-height-rule: exactly;">Pencak silat, Usia prasekolah